Test Anxiety Among Students of Upper Primary Level - Singh, Sunita (THE PRIMARY TEACHER, 2018)
Test anxiety refers to a symptom or group of symptoms that can induce ‘worries’ and tension, and sometimes physiological symptoms like blood pressure increase or in some cases decrease (Kazdin, 2000). The main objective of this paper is to find out the test anxiety among students of upper primary level. To achieve this objective, the researcher used a tool named ‘test anxiety scale’. The tool consists of 55 items. The reliability of the test was found to be 0.81 by the split-half method, and the content and face validity of the test were also established. A purposive sampling technique was used to select a total of 100 students. It was found that half of the samples have an average level of test anxiety. These results reveal that nearly half the sample of students in the present study experienced Average Test Anxiety. This indicates that the other half were not unduly stressed or anxious about their examination or test. The remaining half of the sample of students was distributed nearly equally into the other two categories, i.e., Lower Test Anxiety and Higher Test Anxiety. The paper concludes by stating that anxiety does not suddenly manifest itself at the upper primary stage; it quite certainly originates at the primary stage. Parents, teachers and all stakeholders need to ensure that assessment should not lead to an undue increase in stress levels at the primary stage, for this would have repercussions in later academic life.